Pengaruh Value Added of Capital Employed, Human Capital Structural Capital Value Added, Intelectual Coeffisients, Return on Assets terhadap Nilai Perusahaan - Ghadah, Ghadah; Mufidah, Mufidah; Masnun, Masnun; Febrianti, Ira; Adisetiawan, R (Universitas Batanghari Jambi, 2024)
This study examines the effect of the value added of capital employed, human capital structural capital value added, intelectual coeffisients, return on assets on company value. This research takes as its object the companies that are members of the customers goods industry listed on the Indonesia Stock Exchange for the period 2018 - 2022 which have made consecutive profits. Based on the research results, value added of capital employed return on assets influence company value. On the other hand, there are human capital, structural capital value added, intelectual capital which have no effect on company value